(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Recently the iterative forward backward (FB) method has been proposed to solve the magnetic field integral equation (MFIE) for smooth one dimensional (1-D) rough surface. This method has proved to be very efficient, converging in a small number of iterations. Nevertheless, this solution becomes unstable when some obstacle like a ship or a large breaking wave, is included in the original problem has been presented. The generalized forward backward electric field integral equation (EFIE), which is solved using a hybrid combination of the conventional FB method and the method of moments (MoM), the latter of which is only applied over a small region around the obstacle. The GFB method is shown to provide accurate results numerical results show that different random ocean surface greatly affect the backscatter patterns of ship like target, although the patterns tend to have about the some average level. The purpose of the GFB method introduced here is to provide a numerical tool for studying this class of scattering problems.